2015
DOI: 10.1111/ajgw.12123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of berry size on red wine colour and composition

Abstract: Background and Aims According to one of the classical postulates of viticulture, cultivars with smaller berries produce the best red wines. During grape development, some differences at berry level lead to a wide range of fruit heterogeneity at harvest. One source of heterogeneity at harvest is berry size. The aim of this work is to determine if berry size affects the colour and chemical composition of wine. Methods and Results Cabernet Sauvignon grapes were harvested at optimal ripeness, and screened by two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 79 publications
12
29
0
Order By: Relevance
“…The relative proportion of berry tissue masses have also been investigated by Walker et al ., Barbagallo et al . and Gil et al . but without considering the effect of vine water status.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The relative proportion of berry tissue masses have also been investigated by Walker et al ., Barbagallo et al . and Gil et al . but without considering the effect of vine water status.…”
Section: Discussionsupporting
confidence: 90%
“…This topic has been addressed by Roby and Matthews 5 and Cooley et al 20 in Cabernet Sauvignon. The relative proportion of berry tissue masses have also been investigated by Walker et al, 6 Barbagallo et al 7 and Gil et al 2 but without considering the effect of vine water status. The approach of this study was unique in that it was conducted at the berry level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, grape growers and oenologists believe that the lower the berry size, the better its oenological attributes are. Recently, a study found that Cabernet Sauvignon wines made from small berries presented better oenological attributes (higher total soluble solids and phenolics concentrations) than others coming from large and medium-sized berries (Gil et al, 2015). This might have implications for winemaking, since berry size affected the volatile profiles of Merlot and Cabernet (Xie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%